2015
DOI: 10.1155/2015/805706
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Etiology, and Prevention of Late IOL-Capsular Bag Complex Dislocation: Review of the Literature

Abstract: Posterior chamber intraocular lens (PC-IOL) subluxation is uncommon but represents one of the most serious complications following phacoemulsification. Late spontaneous IOL-capsular bag complex dislocation is defined as occurring three months or later following cataract surgery. Unlike early IOL dislocation, late spontaneous IOL dislocation is due to a progressive zonular dehiscence and contraction of the capsular bag many years what seemed to be uneventful surgery. In recent years, late in-the-bag IOL subluxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 75 publications
2
108
1
11
Order By: Relevance
“…In uveitis, an altered blood-aqueous barrier may allow cytokines to stimulate epithelial cell proliferation and increase capsule contraction. In addition, inflammation of the ciliary body could destabilize the zonules at their insertion sites [10].…”
Section: Discussionmentioning
confidence: 99%
“…In uveitis, an altered blood-aqueous barrier may allow cytokines to stimulate epithelial cell proliferation and increase capsule contraction. In addition, inflammation of the ciliary body could destabilize the zonules at their insertion sites [10].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pseudoexfoliation holds further significance aside from the risk of intraoperative complications, however. Ascaso et al observed that more than half of all late (greater than three months after surgery) IOL-capsule complex dislocations are attributable to pseudoexfoliation syndrome (38). …”
Section: Ocular Manifestationsmentioning
confidence: 99%
“…Dislocation of an intraocular lens (IOL) implanted during cataract surgery is one of the problems encountered during surgery [1]. Although this complication occurs frequently in eyes with an out-of-the-bag IOL with a partially damaged lens capsule, weakness or rupture of Zinn's zonule could cause displacement of the capsular bag that contains an IOL [2,3].…”
Section: Introductionmentioning
confidence: 99%